2017
DOI: 10.1039/c7ra01986f
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic isovaleryl sucrose esters from Ainsliaea yunnanensis: reduction of mitochondrial membrane potential and increase of reactive oxygen species levels in A549 cells

Abstract: Eight isovaleryl sucrose esters, named ainslosides A-H (1-8), were isolated from Ainsliaea yunnanensis Franch. Their structures, including the absolute configurations of the sugar residues, were elucidated by extensive analysis of NMR spectra and acid hydrolysis. All compounds were tested in vitro for cytotoxicity against four human tumour cell lines, A549, HCT116, MDA-MB-231, and BEL7404. Among the compounds tested, ainsloside B (2) showed potent cytotoxicity against the A549 cell line with an IC 50 value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The ROS plays a key role in inducing cancer cells to undergo mitochondria‐mediated apoptosis. [ 14,18,19 ] In this study, intracellular ROS level was detected by fluorescence microscopy following staining with DCFH‐DA. The results (Figure 6) showed that the ROS level was increased in a dose‐dependent manner after incubated with different concentration of pyoluteorin for 24 h. To further verify whether the cell apoptosis was associated with generation of intracellular ROS, we analysed the ROS fluorescence imaging by laser scanning confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The ROS plays a key role in inducing cancer cells to undergo mitochondria‐mediated apoptosis. [ 14,18,19 ] In this study, intracellular ROS level was detected by fluorescence microscopy following staining with DCFH‐DA. The results (Figure 6) showed that the ROS level was increased in a dose‐dependent manner after incubated with different concentration of pyoluteorin for 24 h. To further verify whether the cell apoptosis was associated with generation of intracellular ROS, we analysed the ROS fluorescence imaging by laser scanning confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Previous phytochemical studies of this species have led to the isolation and identification of sesquiterpenoids, triterpenoids, isovaleryl sucrose esters and three other components [6,7,8,9,10,11]. Sesquiterpenoids are an important type of constituent contributing to bioactivity, and have been revealed to possess potential anti-inflammatory activity [6,8].…”
Section: Introductionmentioning
confidence: 99%